Getting a GRIP on work-related stress: design and evaluation of a nature inspired relaxation space. (2016) - Garde-Perik, Evelien Van de; Trevia, Federico; Henriksson, Adam; Geurts, Luc; Ullerup, Helle
The GRIP project takes an open innovation approach by multiple design iterations together with multiple experts in a relatively new area for design (work-related stress). The GRIP relaxation space offers employees an adaptive environment inspired by nature that reacts to people's presence and creates a personal environment, varying in size, soundscape and animated light. The environment stimulates paced breathing, meditation and helps employees to become more aware and in control of their personal response to stressors and relaxation. The design has been evaluated by 23 experts with backgrounds in design, research and healthcare. These evaluations resulted in very positive responses regarding the low effort required and the high quality of the relaxation experience provided by the design. The open approach has resulted in a design of the relaxation space that provides a platform for further exploration and innovation within and beyond the domain of work-related stress.